Pendekatan Data Envelopment Analysis untuk Mengukur Kinerja Keuangan Bank BJB Periode Tahun 2015-2020 - Fauziah Salma; Djoni Djatnika; Fifi Afiyanti Tripuspitorini (Indonesian Journal of Economics and Management, 2022)
BJB Bank is the largest RDB that can generate profits and increase its assets during the COVID-19 pandemic when economic activity is sluggish. The purpose of this research is to solve the evaluation of financial performance by using the data envelopment analysis (DEA) method to view the efficiency of the company's financial management through the input-output bank BJB during the period 2015-2020. This study uses an intermediary approach. The input variables used are third-party funds, human resources, and fixed assets, while the output variables are loans. The research method used in this study is quantitative description. The author uses auxiliary data obtained from the 2015-2020 financial statements of BJB Bank. The survey results show that from 2015 to 2020, the overall average bank BJB reached 99.67% of a relatively efficient state.